Study on Vibration Control and Parameters Influence of Cable Inerter Viscous Damping System - Ruoyu Zhang; Meigen Cao (Shock and Vibration)
In this study, a single-degree-of-freedom (SDOF) model with cable inerter viscous damper (CIVD) is established, and the vibration control equations and frequency response functions are established. Then, the influence of parameters, including inertia mass ratio, additional damping ratio, and stiffness ratio, is studied. Finally, the dynamic time history analysis of SDOF with CIVD under earthquake and fluctuating wind load is carried out to verify the damping performance of CIVD. The research shows that the additional mass and damping of CIVD can be amplified hundreds of times through the rotation, so as to realize the lightweight and high efficiency of the damper and make up for the engineering defects of the traditional TMD system. Meanwhile, when designing CIVD, the inertia mass ratio and additional damping ratio should be reduced as much as possible under the condition of meeting the target damping ratio. The CIVD can significantly suppress the resonance response of the structure and the continuous vibration response in the stable state. The peak displacement can be reduced by 30%–50%. Installing the cable and inerter element can control only the structural vibration, but it cannot reduce the amplitude in the steady state. The CID can control the inertial force output of the original structure, but the rotating speed of the inerter element is high, and the shaking speed of the original structure is fast. Therefore, in order to control the acceleration, velocity, and displacement of the original structure at the same time, we must add the appropriate inerter, additional damping, and additional stiffness.